2016
DOI: 10.1186/s40623-016-0483-4
|View full text |Cite
|
Sign up to set email alerts
|

Building damage survey and microtremor measurements for the source region of the 2015 Gorkha, Nepal, earthquake

Abstract: We performed a damage survey of buildings and carried out microtremor observations in the source region of the 2015 Gorkha earthquake. Our survey area spans the Kathmandu valley and areas to the east and north of the valley. Damage of buildings in the Kathmandu valley was localized, and the percentage of the totally collapsed buildings was less than 5 %. East of the Kathmandu valley, especially in Sindhupalchok district, damage of buildings was more severe. In the center of Chautara and Bahrabise, towns in Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The epicenter was located in the eastern area of the Gorkha District at Barpak, Gorkha, and the hypocenter was at a depth of approximately 8.2 km (USGS, 2015). Many masonry buildings were seriously damaged in historic cities and towns in the Kathmandu Valley (Ohsumi et al, 2016;Yamada et al, 2016;Bhagat et al, 2018). The Nepal Disaster Risk Reduction Portal has reported the aggregate number of disaster victims (Nepal Disaster Risk Reduction Portal; as of 2022) to be 8,962 people killed, 22,302 injured, and 195 missing in all regions of Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…The epicenter was located in the eastern area of the Gorkha District at Barpak, Gorkha, and the hypocenter was at a depth of approximately 8.2 km (USGS, 2015). Many masonry buildings were seriously damaged in historic cities and towns in the Kathmandu Valley (Ohsumi et al, 2016;Yamada et al, 2016;Bhagat et al, 2018). The Nepal Disaster Risk Reduction Portal has reported the aggregate number of disaster victims (Nepal Disaster Risk Reduction Portal; as of 2022) to be 8,962 people killed, 22,302 injured, and 195 missing in all regions of Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…When the authors executed research of damage of civil/architectural structures caused by Nepal Gorkha Earthquake in 2015, it was confirmed that the retaining walls using gabions are widely used in Nepal [2]. Araniko Highway, objective of the research, is located about 10km west of the place where the biggest aftershock occurred (Dolakha county), and at Barhabise along the Highway 42% of houses were completely destroyed [3]. Almost all of the retaining walls using gabions were gravity type that gabions were straightly piled up, and some of them suffered from stick out or fall forward that are considered to be affected by external factor such as earthquake (Nepal Gorkha Earthquake) and rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…The strong motion station at Tumaco, Colombia which is located 350 km from the damaged cities was the closest station. In the 2015 Gorkha (Nepal) M w 7.8 earthquake, many buildings were damaged in the densely populated Chautara region (Yamada et al 2016). The nearest station (i.e., KATNP) was located 28 km away from this region.…”
Section: Introductionmentioning
confidence: 99%